The Effectiveness of Smoking Corner in RT 001 RW 004 Tirta Siak Pekanbaru - Aryantiningsih, D S; Syafitri, Y (KnE Life Sciences, 2019)
Indonesia is facing a big challenge which is Triple Burden, because there are still inflectional diseases and the raising of non-contagious disease, and a disease that should have been resolved, reappeared. In this situation, the government literally has already made a community movement, which is healthy life community movement to decrease the number of death and illnesses. In the early step, the community movement started on focusing in a 30 minutes’ physical movement per day, consuming vegetable and fruit; and regularly do the medical check up. According to the health profile, Case Notification Rate (CNR) BTA (+) in Titra Siak is about 80,4 per 100.000 citizen and Case Notification Rate (CNR) of all TB case is about 168 per 100.000 citizen. Besides that, rate healing number of TB is 0%, diarrhea case reaches 15,7%, hypertension hits 14,8%, obesity reaches 29%, and BCG vaccination reaches 88,4 %. The aim of this research is to measure the effectiveness of smoking corner. This writing is a Quasi experiment with One Group pretest-postest design. Population is all the smoker in the RT 001 RW 004 which are 62 people, total population is the sampling technique. The research result showed that the mean of citizen’s knowledge before the smoking corner existed is 59,84% with deviation standard is 11,379, the mean after smoking corner existed is 72,74 with deviation standard is 6,317, pvalue = 0,00001 (< 0,05). Meanwhile the citizen perception before the smoking corner existed, the mean is 60,81 with 11,636 in standard deviation, after the smoking corner existed, the mean is 74,68 with 10,036 in deviation standard, P Value = 0,00001 (< 0,05). It could be concluded that there is a significant different between knowledge and the perception about smoking corner before and after the smoking corner existed. Keywords: effectiveness, smoking corner, knowledge, perception